PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP PRESTASI BELAJAR SISWA DI MTS NEGERI 1 KOTA TERNATE - Adiyana Adam (Media Bina Ilmiah, 2023)
The purpose of education is not only to educate students but also to develop the potential of students. Therefore, every teacher in the teaching and learning process in each education implementation unit must really understand every material that will be taught besides that every subject teacher must also master the use of learning media in supporting the achievement of learning objectives. This research uses qualitative methods with the type of research is field research or field research. The results of this study are that at MTsN 1 Kota Ternate, there are adequate learning media and the use of these media has been mastered by every teacher. The constraints faced are learning achievement factors which are not only internal student factors but also external factors